Sacred Weather : Atmospheric essentialism in the work of John McGahern - Campbell, Niamh (Book collections on Project MUSE., 2019)
"Is there such a thing as essential Irishness, something which can be experienced, invested in, and politically weaponised? Sacred Weather proposes to take this idea seriously, or literally, by proposing an objective correlative to 'Irishness' in certain atmospheric effects - or Stimmung - as these are depicted in literature, art, and film. By filtering the concept of pure pleasure, through recent writings on Marxist and affect theory by Antonio Negri, as well as the eco-critical writings of Timothy Morton, this work develops atmospheric essentialism as a theoretical template through which Irish Studies might radically, creatively, and imaginatively reconsider the idea of Irishness as an experience in itself. It does this by applying and expanding upon the operations of atmospheric essentialism in the work of the Irish novelist and short-story writer John McGahern and, in this way, proposing an equally radical intervention in current considerations of, and consensus on, the work of this writer. The readings are original, risky, and intended to start conversation"--